2007
DOI: 10.1097/qad.0b013e328012b896
|View full text |Cite
|
Sign up to set email alerts
|

Negative mucosal synergy between Herpes simplex type 2 and HIV in the female genital tract

Abstract: The findings suggest a mucosal vicious circle in which HSV2 infection increases HIV target cells in the genital mucosa, subsequent HIV infection impairs HSV2 mucosal immune control, and local HSV2 reactivation enhances both HSV2 and HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
148
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 48 publications
4
148
0
Order By: Relevance
“…Given the breadth of the study populations examined and consistent results, it is unlikely that residual confounding associated with sexual behaviors accounts for the association between HSV-2 and HIV-1 acquisition, suggesting that other mechanisms, possibly immunological susceptibility, may partially explain the observed relationships (Corey et al 2004). In a recent study, HSV-2 +/HIV− women showed an increase in genital mucosal target cells populations that are known to enhance HIV infection, even in the absence of genital ulceration or HSV2 reactivation (Rebbapragada et al 2007). Kaul et al has reviewed the evidence for negative mucosal synergy between HIV and HSV-2 (Kaul et al 2007).…”
Section: Stress and Acquisition Of Hivmentioning
confidence: 97%
“…Given the breadth of the study populations examined and consistent results, it is unlikely that residual confounding associated with sexual behaviors accounts for the association between HSV-2 and HIV-1 acquisition, suggesting that other mechanisms, possibly immunological susceptibility, may partially explain the observed relationships (Corey et al 2004). In a recent study, HSV-2 +/HIV− women showed an increase in genital mucosal target cells populations that are known to enhance HIV infection, even in the absence of genital ulceration or HSV2 reactivation (Rebbapragada et al 2007). Kaul et al has reviewed the evidence for negative mucosal synergy between HIV and HSV-2 (Kaul et al 2007).…”
Section: Stress and Acquisition Of Hivmentioning
confidence: 97%
“…Cytobrush samples were obtained as described in ref. 31 under a study protocol approved by the Research Ethics Boards at the University of Toronto and the Kenyatta National Hospital (Nairobi, Kenya). Retinoic acid was obtained from Sigma Chemical.…”
Section: Methodsmentioning
confidence: 99%
“…Also, activated CD4 T lymphocytes and macrophages, which act as target cells for HIV-1 attachment and entry, infiltrate genital herpes lesions in epidermis and/or dermis (11)(12)(13). Increases in these HIV-1 target cell populations are evident in the genital mucosa even in the absence of clinical HSV-2 disease, during asymptomatic shedding, and also persist between lesions (14), suggesting that a persistent state of increased mucosal susceptibility is induced by HSV-2 infection. Indeed, HIV-1 has been shown to replicate to much higher levels in cells extracted from mucosa between lesions than from control mucosa.…”
mentioning
confidence: 99%